2014
DOI: 10.2478/rela-2014-0004
|View full text |Cite
|
Sign up to set email alerts
|

Formulaic Sequences as Fluency Devices in the Oral Production of Native Speakers of Polish

Abstract: In this paper we attempt to determine the nature and strength of the relationship between the use of formulaic sequences and productive fluency of native speakers of Polish. In particular, we seek to validate the claim that speech characterized by a higher incidence of formulaic sequences is produced more rapidly and with fewer hesitation phenomena. The analysis is based on monologic speeches delivered by 45 speakers of L1 Polish. The data include both the recordings and their transcriptions annotated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…The benefits of mastering formulaic sequences have been repeatedly cited in the literature (e.g., Durrant, 2008;Wray, 2000). For example, Martinez and Schmitt (2012) highlight four key benefits for formulaic sequences that were also supported by empirical evidence; (1) making up a large proportion of any discourse (e.g., 58.6% of spoken text and 52.3% of written text by Erman and Warren (2000), (2) realizing a multitude of meanings and functions (e.g., signposts of discourse organization like "on the other hand," and commonly believed truths such as "Money talks"), (3) promoting efficient and effective communication as formulaic language is easier and faster to understand and produce (e.g., Conklin and Schmitt, 2008;Jiang and Nekrasova, 2007), and (4) enhancing productive fluency (e.g., Guz, 2014). The proven centrality of this phenomenon to communication has called for investigating its use by second/foreign language learners whose effective and efficient language use highly relies on adequate knowledge of formulaic language.…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of mastering formulaic sequences have been repeatedly cited in the literature (e.g., Durrant, 2008;Wray, 2000). For example, Martinez and Schmitt (2012) highlight four key benefits for formulaic sequences that were also supported by empirical evidence; (1) making up a large proportion of any discourse (e.g., 58.6% of spoken text and 52.3% of written text by Erman and Warren (2000), (2) realizing a multitude of meanings and functions (e.g., signposts of discourse organization like "on the other hand," and commonly believed truths such as "Money talks"), (3) promoting efficient and effective communication as formulaic language is easier and faster to understand and produce (e.g., Conklin and Schmitt, 2008;Jiang and Nekrasova, 2007), and (4) enhancing productive fluency (e.g., Guz, 2014). The proven centrality of this phenomenon to communication has called for investigating its use by second/foreign language learners whose effective and efficient language use highly relies on adequate knowledge of formulaic language.…”
Section: Introductionmentioning
confidence: 99%
“…Essentially, sequence-internal markers capture some arbitrary irregularity of the string, which sets it apart from other, productively generated sequences of words. For example, investigations of the articulatory properties of formulaic strings have shown that compared to non-formulaic, novel strings, formulaic sequences display a set of idiosyncratic articulatory characteristics which include: reduced susceptibility to internal pausing and hesitation phenomena (Dahlmann 2009;Dahlmann and Adolphs 2009;Erman 2006Erman , 2007Guz 2014;Wray 2004); alignment with intonational units (Lin 2010;Lin and Adolphs 2009); idiosyncratic accentual patterns (Ashby 2006;Wells 2006) and susceptibility to phonetic reduction (Bybee 1998(Bybee , 2001). Semantic compositionality is another sequence-internal property that has been frequently prioritised as the main indicator of the formulaic status.…”
Section: Sequence-internal Criteriamentioning
confidence: 99%